THE EFFECT OF PROBLEM BASED LEARNING AND PERFORMANCE ASSESSMENT ON STUDENTSâ READING AND WRITING COMPETENCIES - ., I PUTU SUYOGA DHARMA; ., Prof. Dr. A. A. I. Ngurah Marhaeni,MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris, 2014)
Studi eksperimen ini bertujuan untuk menginvestigasi pengaruh pembelajaran berbasis masalah dan asesmen kinerja terhadap kompetensi membaca dan menulis siswa kelas sepuluh SMAN 1 Mengwi pada tahun ajaran 2011/2012. Penelitian ini menggunakan rancangan 2x2 faktorial. 96 siswa dilibatkan sebagai sampel penelitian. Mereka dipilih dengan teknik sampling acak. Data kompetensi membaca dan menulis dikumpulkan melalui tes essay. Data yang diperoleh dianalisis dengan Analysis Varian Multivariat (MANAVA) Temuan penelitian ini adalah 1) pembelajaran berbasis masalah berpengaruh secara signifikan terhadap kompetensi membaca dan menulis siswa yang terjadi secara simultan dan terpisah, 2) asesmen kinerja berpengaruh secara signifikan terhadap kompetensi membaca dan menulis siswa yang terjadi secara simultan dan terpisah, 3) terdapat interaksi signifikan antara model pembelajaran dan tipe asesmen terhadap kompetensi membaca dan menulis yang terjadi simultan dan terpisah, 4) tidak terdapat interaksi signifikan antara model pembelajaran dan tipe asesmen terhadapak kompetensi membaca siswa, 5) terdapat interaksi signifikan antara model pembelajaran dan tipe asesmen terhadapak kompetensi menulis siswa.Kata Kunci : pembelajaran berbasis masalah, asesmen kinerja, kompetensi membaca, kompetensi menulis This experimental study aimed at investigating the effect of Problem Based Learning and Performance Assessment on reading and writing competencies of the tenth grade students of SMAN 1 Mengwi in the academic year 2011/2012. This research applied 2x2 factorial design. 96 students were selected as sample through random sampling. Data of studentsâ reading and writing competencies were collected by using essay tests. The studentsâ answers were scored by using analytical scoring rubric. The acquired data were analyzed statistically by Multivariate Analysis of Variance (MANOVA) at 5% significance level. This research discovers: 1) there is a significant effect of Problem Based Learning which occurs simultaneously and separately on studentsâ reading and writing competencies, 2) there is a significant effect of performance assessment which ocurs simultaneously and separately on studentsâ reading and writing competencies, 3) there is a significant interaction between teaching model and assessment type on studentsâ reading and writing competencies which occurs simultaneously, 4) there is no significant interaction between teaching model and assessment type on studentsâ reading competency, and 5) there is a significant interaction between teaching model and assessment type on studentsâ writing competency.keyword : Problem Based Learning, Performance Assessment, reading competency, writing competency